BASNEF behavioral transformation: effect of empowerment program on children’s knowledge, attitude, self-efficacy, and practice of nail biting - Zohour Ibrahim Rashwan; Hamida Ahmed Mostafa Darweesh; Fatma Ahmed Elsobky; Samah Abdallah Mohamed Amer; Mabrouka Attia Ali Nada (BMC Pediatrics)
Abstract Background Nail-biting or onychophagia is a common phenomenon affecting children. Excessive nail biting is associated with several adverse consequences beyond mere appearance. The aim of this study is to evaluate the effect of an empowerment program based on the BASNEF model on children’s knowledge, attitude, self-efficacy, and nail-biting practice. Method A quasi-experimental study was conducted in the pediatric wards of Menoufia University Hospital and Benha University Hospital. A convenience sample of 135 children (6 to 18 years) was randomly assigned to the study or control group who received routine care. To effectively measure the dependent variables, four questionnaires were developed and tested for content validity, stability reliability and internal consistency. Exploratory Factor Analysis (EFA) identified the underlying factors while the findings of the Confirmatory Factor Analysis (CFA) demonstrated a satisfactory fit. The researcher developed the session objectives, learning activities and designed a booklet with relevant content. The participants of the study group were divided into sub-groups (six children and their mothers) who attended four empowerment sessions based on the BASNEF model, emphasizing (a) age-appropriate information, (b) fostering a positive attitude towards quitting nail-biting, (c) discovering the subjective norms, perceived social expectations, and influences of nail-biting behaviors, and (d) equipping children with enabling factors to quit. The comparison between the two groups was done using the Mann-Whitney (U) test, while the Wilcoxon Signed Rank test conducted for the intragroup comparison. Results There was a significant improvement in knowledge about nail-biting among children in both groups and a noticeable decline in the nail-biting habits/practices among children in the study group (22.42 ± 5.69) compared to the control group (42.76 ± 6.75). The attitude scores towards nail-biting significantly improved among children in the study group compared to the control group with appositive impact on children’s self-efficacy in controlling the habit (P < 0.001 for each). Conclusion The empowerment program based on the BASNEF model effectively improved children’s knowledge, attitude, self-efficacy, and practice of nail biting. Trial registration number Trial registration number: NCT06471153, ClinicalTrails.gov, Retrospectively registered June 18th, 2024), URL of trial registry record: https://clinicaltrials.gov/ct2/show/NCT06471153 .